FAKTOR YANG MEMENGARUHI DISIPLIN SISWA DI SEKOLAH MAN SALIDO KABUPATEN PESISIR SELATAN - Nurdina, Nurdina; Erita, Yeni; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
Nurdina, (2013). Factors Affecting Student Discipline in Schools MAN Salido South Coastal District. Geography Education Program STKIP PGRI West Sumatra.This study aimed to obtain information, analyze and discuss data on the factors that affect school discipline of students in the South Coastal District MAN Salido. This type of research was descriptive correlational. The study population was all students and teachers MAN Salido in 2012. Students are referred to here are students, all students of class X, XI, XII consisting of local, amounting to 7 748 people. The research sample was taken with a random sampling technique with 15% proportion of the sample is determined so that total sample was 101 students. Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) there are significant student interest in the discipline of students MAN Salido South Coastal District for t> t table (3.085> 1.662), the strength of the relationship is low (r = 0.296) and a very small contribution (8.88%), (2) there are significant motivation of students to discipline students MAN Salido South Coastal District since t> t table (3.737> 1.662). Power relations are categorized (r = 0.352) and a very small contribution (12.4%), (3) there is the influence of students attitudes toward student discipline MAN Salido South Coastal District since t> t table (5.169> 1.662). Power relations were moderate (r = 0.461) and the amount of the contribution is very small (21.3%) and (4) there is a significant and positive influence student interest, motivation and attitudes of students together to discipline students MAN Salido South Coastal District because Fhitung> F table (12.509> 3.150). Strength of the relationship between these three variables to discipline students MAN Salido South Coastal District includes medium category (r = 0.528), whereas the contribution .